The genetics of folate metabolism and maternal risk of birth of a child with Down syndrome and associated congenital heart defects - Coppedè, Fabio (Frontiers in Genetics, 2015)
Almost 15 years ago it was hypothesized that polymorphisms of genes encoding enzymes involved in folate metabolism could lead to aberrant methylation of peri-centromeric regions of chromosome 21, favoring its abnormal segregation during maternal meiosis. Subsequently, more than 50 small case-control studies investigated whether or not maternal polymorphisms of folate pathway genes could be risk factors for the birth of a child with Down syndrome (DS), yielding conflicting and inconclusive results. However, recent meta-analyses of those studies suggest that at least three of those polymorphisms, namely MTHFR 677C>T, MTRR 66A>G, and RFC1 80G>A, are likely to act as maternal risk factors for the birth of a child with trisomy 21, revealing also complex gene-nutrient interactions. A large-cohort study also revealed that lack of maternal folic acid supplementation at peri-conception resulted in increased risk for a DS birth due to errors occurred at maternal meiosis II in the aging oocyte, and it was shown that the methylation status of chromosome 21 peri-centromeric regions could favor recombination errors during meiosis leading to its malsegregation. In this regard, two recent case-control studies revealed association of maternal polymorphisms or haplotypes of the DNMT3B gene, coding for an enzyme required for the regulation of DNA methylation at centromeric and peri-centromeric regions of human chromosomes, with risk of having a birth with DS. Furthermore, congenital heart defects (CHD) are found in almost a half of DS births, and increasing evidence points to a possible contribution of lack of folic acid supplementation at peri-conception, maternal polymorphisms of folate pathway genes, and resulting epigenetic modifications of several genes, at the basis of their occurrence. This review summarizes available case-control studies and literature meta-analyses in order to provide a critical and up to date overview of what we currently know in this field.